(untitled) (Oxford, 1964)
As China's international status grows, its civilization excites an increasing interest from the outside world. The Legacy of China is the perfect solution for anyone in need of a non-textbook introduction to the world's legacies from China in the major realms of spirit and intellect. This highly-praised work includes essays by eminent experts like Joseph Needham, A. C. Graham, Michael Sullivan and Patrick Hanan on science, philosophy, art and literature.
Keywords: Trung Quốc,China; Văn minh,Civilization